2021
DOI: 10.1038/s41388-021-02121-9
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase O-GlcNAcylation: a molecular mechanism of 5-FU sensitization in colorectal cancer

Abstract: Alteration of O-GlcNAcylation, a dynamic post-translational modification, is associated with tumorigenesis and tumor progression. Its role in chemotherapy response is poorly investigated. Standard treatment for colorectal cancer (CRC), 5-fluorouracil (5-FU), mainly targets Thymidylate Synthase (TS). TS O-GlcNAcylation was reported but not investigated yet. We hypothesize that O-GlcNAcylation interferes with 5-FU CRC sensitivity by regulating TS. In vivo, we observed that combined 5-FU with Thiamet-G (O-GlcNAca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…(2021) demonstrated that cisplatin enhances UDP-GlcNAc production and global O -GlcNAcylation levels in vitro and in vivo by OGT, GFAT1 activation, and OGA inhibition ( 33 ). Conversely, we recently demonstrated that 5-FU decreases intracellular O -GlcNAcylation in vitro by reducing OGT at both protein and transcriptional levels but also in vivo most likely by reducing OGT activity ( 34 ). Owing to the fact that OGT enzymatic activity is inhibited by elevated UDP, UTP, and UDP-GlcNAc ( 35 ), we suggest that 5-FU metabolites may inhibit OGT by producing fluorinated derivates or uridine compounds ( 36 ).…”
Section: Impact Of Anti-cancer Therapies On O -Glc...mentioning
confidence: 99%
See 3 more Smart Citations
“…(2021) demonstrated that cisplatin enhances UDP-GlcNAc production and global O -GlcNAcylation levels in vitro and in vivo by OGT, GFAT1 activation, and OGA inhibition ( 33 ). Conversely, we recently demonstrated that 5-FU decreases intracellular O -GlcNAcylation in vitro by reducing OGT at both protein and transcriptional levels but also in vivo most likely by reducing OGT activity ( 34 ). Owing to the fact that OGT enzymatic activity is inhibited by elevated UDP, UTP, and UDP-GlcNAc ( 35 ), we suggest that 5-FU metabolites may inhibit OGT by producing fluorinated derivates or uridine compounds ( 36 ).…”
Section: Impact Of Anti-cancer Therapies On O -Glc...mentioning
confidence: 99%
“…OGT was also identified in a cluster of co-expressed genes associated with 5-FU resistance in colorectal cancer (CRC) ( 79 ). Moreover, the 5-FU pathway actors SLC29A1 ( 80 ), TP ( 10 ), TK ( 81 , 82 ), and TS ( 34 ) are direct targets for O -GlcNAcylation ( Figure 2 ). Nevertheless, modified sites and roles of this PTM on these proteins as well as their impacts on 5-FU sensitivity are largely not elucidated yet.…”
Section: Impact Of O -Glcnacylation On Response To...mentioning
confidence: 99%
See 2 more Smart Citations
“…The drug 5-fluorouracil (5-FU) is a synthetic fluorinated pyrimidine analog that is widely used in the treatment of cancers including colorectal cancer (CRC), breast cancer, and respiratory and digestive tract cancers ( 6 ). This drug is mainly converted into active metabolites such as fluorodeoxyuridine monophosphate (FdUMP), which inhibits the action of thymidylate synthase (TYMS), a rate-limiting enzyme of DNA synthesis, ultimately leading to cell damage ( 7 ). However, acquired drug resistance is the main issue limiting its clinical application ( 8 ).…”
Section: Introductionmentioning
confidence: 99%